Relative contributions of galactic cosmic rays and lunar proton "albedo" to dose and dose rates near the Moon. Issue 11 (14th November 2013) - Spence, Harlan E.; Golightly, Michael J.; Joyce, Colin J.; Looper, Mark D.; Schwadron, Nathan A.; Smith, Sonya S.; Townsend, Lawrence W.; Wilson, Jody; Zeitlin, Cary
Abstract [1] We use validated radiation transport models of the Cosmic Ray Telescope for the Effects of Radiation instrument and its response to both primary galactic cosmic rays (GCR) and secondary radiation, including lunar protons released through nuclear evaporation, to estimate their relative contributions to total dose rate in silicon (372 μGy/d) and dose equivalent rate at the skin (2.88 mSv/d). Near the Moon, we show that GCR accounts for ~91.4% of the total absorbed dose, with GCR protons accounting for ~42.8%, GCR alpha particles for ~18.5%, and GCR heavy ions for ~30.1%. The remaining ~8.6% of the dose at Lunar Reconnaissance Orbiter altitudes (~50 km) arises from secondary lunar species, primarily "albedo" protons (3.1%) and electrons (2.2%). Other lunar nuclear evaporation species contributing to the dose rate are positrons (1.5%), gammas (1.1%), and neutrons (0.7%). Relative contributions of these same species to the total dose equivalent rate in skin, a quantity of more direct biological relevance, favor those with comparatively high quality factors. Consequently, the primary GCR heavy ion components dominate the estimated effective skin dose. Finally, we note that when considering the lunar radiation environment, although the Moon blocks approximately half of the sky, thus essentially halving the absorbed dose rate near the Moon relative to deep space, the secondary radiation created by the presence of the Moon adds back a small, but measurable, absorbed dose (~8%) that can and should be now accounted for quantitatively in radiation risk assessments at the Moon and other similar exploration targets.